Human Right to Internet Access in Healthcare in the "Right to Health Concept": Legal Issues - Shevchuk, Oleksandr; Zui, Valentyna; Maryniv, Ivanna; Davydenko, Svitlana; Mokhonchuk, Sergii (European Journal of Sustainable Development, 2021)
This work reveals the features of the administrative and legal regulation of the human right to access the Internet in the concept of the right to health